Lithuanian Olympic Basketball Players' Nutrition during the Training Mezzo-Cycles Designed for Strength Training - Marius Baranauskas; Linas Tubelis; Rimantas Stukas; Edmundas Švedas; Laimutė Samsonienė; Diana Karanauskienė (Lithuanian Sports University, 2018)
Research  background  and  hypothesis.  Unbalanced  nutritional  status,  incorrect  qualitative  and  quantitative content of nutritional and bioactive substances (nutrition value) for athletes in strength and speed sports can have a negative impact on acid-base homeostasis and physical working performance. Hypothesis - there is a dietary acid- base balance in the Lithuanian Olympic basketball team players' food rations. Research aim was to assess dietary acid-base balance in Lithuanian high-performance basketball players during the training mezzo-cycles designed for strength training. Research methods. In the general preparation period, Lithuanian Olympic Team basketball players (n = 52), aged 18.0 ± 1.9 years, training 197.9 ± 58.7 min a day, 6 days a week on average, were tested. Body composition  analysis  of  athletes  was  performed  using  bioelectrical  impedance  analysis  (BIA)  method. Applying  the  survey  method we investigated and assessed the nutritional status of basketball players, possible effect of their dietary intake  on potential renal acid load (PRAL) and net endogenous acid production (NEAP). Research results. The dietary PRAL of more than half (67.3%) of subjects was positive (8.5 ± 49.0 mEq/day). Basketball players' protein intake was positively related to dietary PRAL (r = 0.408, p = 0.003). Protein intake of 20.5% of male basketball players on average was 2.6 ± 0.7 g/kg body weight, and their dietary PRAL was 75.5 ± 22.8 mEq/day, NEAP - 128.5 ± 23.7 mEq/day. Discussion and conclusions. If high-protein diet (protein intake meets 1.8-2.0 g/kg BW) is followed, basketball players' nutritional habits should be changed. Athletes are recommended to consume significantly more fresh fruits and vegetables and/or enrich the normal diet by sodium bicarbonate and/or beta-alanine dietary supplements. Keywords: basketball, acid-base balance, renal acid overload.